The mediation effect of stock market performance on the relationship between exchange rate and economic growth in sri lanka - Tharsika, K. (Jaffna Science Association, 2024)
Sri Lanka has recently confronted a severe economic crisis, characterized by a notable decline in GDP growth attributed to inadequate government policies and the impact of COVID-19. Consequently, it is imperative for the Sri Lankan government to formulate a comprehensive plan to stimulate the nation's GDP growth. Previous empirical evidence suggests that exchange rate and stock market performance exert an influence on GDP growth. However, the mediating effect of stock market performance on the relationship between exchange rate and economic growth is globally insufficient. Therefore, there is a need to undertake a study on the mediating effect of stock market performance on the association between exchange rate and economic growth in the Sri Lanka to address this existing gap. The study incorporated quarterly time series data from the World Bank and central bank annual reports spanning the period from 2010 to 2022. It utilised the unit root test, autoregressive distributive lag, and Sobel test to investigate the study's objective. The results revealed that stock market performance significantly mediates between exchange rate volatility and economic growth in Sri Lanka. These findings underscore the importance of the government and policymakers designing appropriate policies concerning exchange rates and stock market performance to enhance Sri Lanka's economic growth.
Keywords: Economic Growth; Exchange Rate Volatility; Stock Market Performance